Scientific 3D visualisation of body during hurdle racing - Muftic, O.; Baksa, S.; Baksa, I. (International Journal of Computer Science in Sport, 2002)
Biomechanical analysis of mechanisms of human motion is very complex and demanding. Virtual 3D models of the kinematic and locomotory system as one of a man, distinguish by digitalised statical and dynamical characteristics which reflect real human characteristics. With the use of authorialy developed program solutions within this work, statical and dynamical body anthropometrical measuring of the male athlete body during hurdle racing have been accomplished. Based on cognition of structure and functions of inner kinematic system of human body, computer kinematic model has been made, which serves as an originating base for construction and animational analysis of virtual 3D character.